Experiential Learning to Promote Student Autonomy at Elementary Level - Hossain, Shaukat Ali; Manzoor, Mehmood Ahmed; Hashmi, Rozina (Journal of Innovation and Research in Primary Education, 2023)
The primary objective of this research is to assess Learners' Autonomy by implementing Experiential Learning in a role-play activity among class 8 elementary students at a private-sector English Medium School. Experiential Learning, which is a learner-friendly approach, has not been extensively explored at the fundamental level. However, its importance, often referred to as "learning by doing" or "hands-on approaches," has been acknowledged in various writings and research. Over time, Experiential Learning has gained popularity among adult learners and is considered crucial in educational institutions. To conduct this study, a thorough review of the literature was conducted, leading to the development of a hypothesis. The research strategy involved the use of a survey, and the study's population comprised students from elementary private schools in Karachi. A straightforward random sampling design was adopted, resulting in a sample size of 118 students as participants. For data collection, two questionnaires were employed: the Experiential Learning Scale (ELS) by Clem and Beasley, and the Learner Autonomous Scale (LAS) by Fletcher and Averill. The data was then analyzed using SPSS, with inferential statistics, correlation, and linear regression methods. The findings revealed a strong correlation between the variables (EL) and (LA). Moreover, at a significance level of 0.05, the overall relationship between all Experiential Learning and Learner Autonomous categories was determined to be moderate. Based on the overall linear regression model, instructors and practitioners are encouraged to incorporate Experiential Learning into their teaching methodologies. Additionally, the study suggests further exploration of the concept of Autonomous Learning through this process, and proposes a comparative study to assess how this approach influences students' engagement in various curricula.